Simbol dan Makna Tradisi Upacara Kematian Nyurup Etnis Tengger Desa Argosari: Daya Tarik Wisata Edukasi Budaya - Martalia, Diana; Pracintya, Ida Ayu Etsa (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
This study explores the symbols and meanings behind the Nyurup death ritual of the Tengger ethnic group in Argosari Village and its potential as an educational cultural tourism attraction. The research employs a qualitative descriptive method with an ethnographic approach, focusing on the symbolism embedded in the offerings (sesaji) used in the ritual. These offerings serve as a form of ritual communication, passing down sacred messages and values from the ancestors to future generations. However, the younger generation’s lack of understanding of these symbols highlights the need for cultural preservation through education. Additionally, the study examines the potential of the Nyurup ritual to attract both domestic and international tourists, enhancing the local economy through cultural tourism. This research concludes that the Nyurup death ritual is not only a spiritual practice but also a significant opportunity for cultural and educational tourism development in the region.